RED ONION COMPRESS FOR REDUCING BODY TEMPERATURE IN EPILEPSY PATIENTS WITH HYPERTERMY - Sandriani Sandriani; Siti Aisyah; Andan Firmansyah (HealthCare Nursing Journal, 2022)
The purpose of this case study is to carry out the intervention of a red compress on an epileptic child with symptoms of hyperthermia. The method used in this research is descriptive qualitative with a case study approach. The subject of this case study is an epileptic child who has hyperthermia. In collecting data conducting interviews, observations, physical examinations, and documentation. The intervention carried out was to compress the onion 2x a day for 3 days of implementation. The results of the case study in the assessment phase of the client found the main complaint, namely hyperthermia. The established nursing diagnosis is hyperthermia associated with an increase in body temperature. In the data obtained prior to the intervention of the onion compress, the client's body temperature was 39.5oC. Nursing interventions were carried out with red onion compresses 2x a day in 3 days of implementation. After being given the onion compress intervention, data on a decrease in body temperature was obtained with objective data obtained at 37.5oC. The conclusion of the non-pharmacological intervention of onion compress in reducing body temperature was proven to be effective with the result that the client's body temperature decreased from 39.5oC to 37.5oC.